2006
DOI: 10.1007/bf02984656
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of regional cerebral blood flow with123I-IMP using one-point venous blood sampling and causality analysis: Evaluation by comparison with conventional continuous arterial blood sampling

Abstract: These results suggest that this method would serve as a convenient and less invasive method of rCBF measurement in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…2 Time course of the radioactivity of the lungs after intravenous injection of 123 I IMP (Ca10) using the initial 123 I IMP circulation image, time series of static images of the brain, and brain SPECT (1). It was demonstrated that the mean CBF values calculated by 123 I IMP ARG method (11,17) using the estimated Ca10 closely correlated with those calculated using Ca10 directly measured with the actual blood sample, and that the mean CBF values calculated by 123 I IMP ARG method using either the directly measured or the estimated Ca10 significantly correlated with those obtained by 15 O-H 2 O PET ARG method (16,19), suggesting that this noninvasive method of es-timating 123 I IMP arterial blood activity for rCBF quantification can be a convenient alternative to the conventional methods requiring arterial blood sampling (8). Thus the method developed in the previous study is an indirect one for the purpose of rCBF quantification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Time course of the radioactivity of the lungs after intravenous injection of 123 I IMP (Ca10) using the initial 123 I IMP circulation image, time series of static images of the brain, and brain SPECT (1). It was demonstrated that the mean CBF values calculated by 123 I IMP ARG method (11,17) using the estimated Ca10 closely correlated with those calculated using Ca10 directly measured with the actual blood sample, and that the mean CBF values calculated by 123 I IMP ARG method using either the directly measured or the estimated Ca10 significantly correlated with those obtained by 15 O-H 2 O PET ARG method (16,19), suggesting that this noninvasive method of es-timating 123 I IMP arterial blood activity for rCBF quantification can be a convenient alternative to the conventional methods requiring arterial blood sampling (8). Thus the method developed in the previous study is an indirect one for the purpose of rCBF quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were studies which indicated that rCBF could be calculated using 123 I IMP and SPECT with venous blood sampling (11,17) or without any blood sampling (7,12,13). In these studies on less invasive methods for rCBF quantification, the rCBF values were compared with those obtained by the conventional methods using 123 I IMP and arterial blood sampling as the reference (7,(11)(12)(13)17).…”
Section: Schlüsselwörtermentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 123 I-IMP is widely used in clinical practice to examine regional cerebral blood flow (rCBF) [3,4]. The input function of 123 I-IMP is calculated based on octanol-water partition coefficients because the lipophilic nature of the 123 I-IMP metabolites gradually decrease as 123 I-IMP is metabolized.…”
Section: Introductionmentioning
confidence: 99%
“…A more simplified 123 I IMP ARG method was also developed using dynamic SPECT and venous blood sampling. 13 In these less-invasive rCBF quantification methods, the results were compared with those obtained by the method using 123 I IMP as the reference. 9 -14 However, there were no reports in which the rCBF values estimated using 123 I IMP without any blood sampling were compared with those obtained by O-15 H 2 O PET ARG method.…”
mentioning
confidence: 99%